К вопросу энергосберегающей реконструкции систем теплоснабжения с паровыми котельными - Товажнянский, Леонид Леонидович; Капустенко, Пётр Алексеевич; Перевертайленко, Александр Юрьевич; Дуич, Н.; Краячич, Г.; Селяков, А. М.; Илюнин, О. О. (НТУ "ХПИ", 2015)
Розглянуто концепцію енергозберігаючої реконструкції парової котельні, що є джерелом тепла для централізованої системи теплопостачання та відпускає пару на технологічні потреби промислового підприємства. Відзначено, що основним заходом є застосування автоматизованої модульної паро водогрійної установки на базі високоефективних пластинчастих теплообмінних апаратів, що дозволяє регулювати постачання тепла користувачам.

The conception of energy saving retrofit for case of steam boilerhouse based district heating system is considered. It was taken into account that boilerhouse supplies the steam for process needs of neighbour site. The main emphasis of the energy saving retrofit is the installation of automatized modular steam/water heating substation based on high effective plate heat exchangers. It lets to manage the heat supply to consumers.
On the problem of steam boilerhouse based district heating system energy saving retrofit
Keywords: теплоэлектроцентрали; ТЭЦ; пароводогрейная установка; пластинчатые теплообменные аппараты; котельный пар